Idioms and proverbs containing color terms in English and Vietnamese from the cultural perspective / Bui Thi Phương Dung; Supervisor: Dr. Le Phuong Thao - Bui, Thi Phương Dung
Being keen on the colors used in idioms and proverbs around the world, including English-speaking countries and Vietnam, the dissertation is named “IDIOMS AND PROVERBS CONTAINING COLOR TERMS IN ENGLISH AND VIETNAMESE FROM THE CULTURAL PERSPECTIVE” from cultural perspective has been chosen by the author. With the purpose of finding and analyzing color words culturally, the study aims at helping English learners and readers deeply comprehend and smoothly use the color words in idioms. , proverbs. As well as their cultural features in English and Vietnamese. The study focuses on solving the main question of what are the fundamental similarities and differences between the English and Vietnamese word of color from cultural standpoint. It is based on the wide range of methods such as qualitative, quantitative, collating and comparing as well as the synthesis methods conducted by data collection, data analysis, and drawing representative conclusions. The writer collect and analyze data from books, newspapers, articles, magazines on the internet and in everyday life, then study them from a semantic and cultural perspective. After being recorded, the writer analyzes them, resulting in the semantics of the word indicating the color in the idiom, the defined proverb, and specific explanation and clarification of the word indicating the color in the idiom, custom English and Vietnamese language. From the research results, the writer tries to learn how to use the words for color in everyday English learning and application in the hope that it will help readers realize the importance of word indicating color language and proverbs in English and Vietnamese in terms of culture in teaching and learning English to have better understanding and discovery. In addition, this study also helps with correcting with students’ mistakes of words and enables having a better understanding of schools of words about colors as well as related words in English and Vietnamese; therefore, the study bears a great potential of becoming basis for other authors to make more intensive studies in the future.